Enhanced gettering of iron impurities in bulk silicon by using external direct current electric field - Lee, W. P.; Teh, E. P.; Yow, H. K.; Choong, C. L.; Tou, T. Y. (2005)
Iron impurities in bulk silicon are found to getter efficiently at the polysilicon layer by an electric field during isothermal annealing. Experimental results show that iron concentration at the polysilicon layer increases to the level that becomes detectable by total reflection x-ray fluorescence (TXRF) spectroscopy. The improved gettering efficiency for iron is attributed mainly to the directional drift of ionic iron interstitials toward the polysilicon gettering sites, under the influence of the applied potential gradient, thus presenting a more effective method for reducing the iron content in silicon.